The Effect of Organizational Citizenship Behavior and Good Corporate Governance on Employee Performance During the Covid-19 Pandemic (Case Study of Panin Dai-ichi Life Timor Branch) - Tiofanny, Caroline (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
This study aims to determine whether Organizational Citizenship Behavior and Good Corporate Governance have significant effect on Employee Performance at Panin Dai-ichi Life Timor Branch. This study uses quantitative data methods and the data source is primary data. The population in this study are all employees who worked at Panin Dai-ichi Life Timor Branch. The sample in this study are permanent employees who work at Panin Dai-ichi Life Timor Branch in total of 30 respondents using purposive sampling methods. Data analysis and testing consist of validity test, reliability test, descriptive statistics, the classical assumption test, multiple regression analysis, partial hypothesis testing (T test) and simultaneous hypothesis testing (F test), and coefficient of determination test. The results of this study indicate that Organizational Citizenship Behavior has a partially significant effect on employee performance with a calculated T-count of 2.659 > T-table 2.048. Good Corporate Governance has a partially significant effect on employee performance with a calculated T-count of 4.423 > T-table 2.048. Organizational Citizenship Behavior and Good Corporate Governance simultaneously have a significant effect on employee performance with a calculated F-count of 40.741 > F-table 3.35 and a regression coefficient value of 73.3%.